Frederick the Great the magnificent enigma - Asprey, Robert B. (New York Ticknor & Fields, 1986)
A very readable account of King Frederick the Great of Prussia.
Introduction -- A prince of the blood, 1712-1730 -- The actor, 1730-1740 -- The first Silesian War, 1740-1742 -- Peace and war, 1742-1746 -- The king rules, 1746-1756 -- The Seven Years' War, 1756-1763 -- The ruler and the realm, 1763-1786.
Maps on lining papers.
Keywords: Frederick -- II -- King of Prussia -- 1712-1786.; Prussia (Germany) -- Kings and rulers -- Biography; Prussia (Germany) -- History -- Frederick II, 1740-1786.